Nutritional Status of Under-Five Children and the Relationship with Household Food Wastage and Food Security in Samarahan, Malaysia - Mohd Mizanur, Rahman; Gahamat, M. F.; Siddiq, M. (Islamic University Malaysia, 2022)
Introduction: Malnutrition is prevalent among children in developing countries. The cause of malnutrition, although complex, can be attributed to demographic factors, household food wastage, and food insecurity. This study aims to determine the under-five nutritional status of children and its association with household food wastage and food security in the Samarahan division in Sarawak, Malaysia. Materials and Methods: This is a cross-sectional study involving 304 children from rural areas of Asajaya and Samarahan District using a random sampling technique. An interviewer-administered questionnaire was used to collect data from the parents. The nutritional status of the children was assessed by anthropometry. IBM SPSS Version 27.0 and WHO Anthro version 3.2.2 were used for data analysis. A p-value < 0.05 was considered statistically significant. Results: Analysis revealed that 9.5% of the children were moderately wasted, followed by 5.9% who were severely wasted; 20.4% were moderately stunted and 8.9% were severely stunted. Hierarchical regression analysis indicated that male gender (AOR = 1.931, 95% CI: 1.139, 3.274; p<0.05), low birth weight (AOR =2.645, 95% CI: 1.245, 5.618, p<0.05), poor appetite (AOR = 2.547; 95% CI: 1.298, 4.995, p<0.05), and preventive attitude (AOR = 0.460, 95% CI: 0.227, 0.929, p < 0.05) of household food wastage appeared to be significant predictors of nutritional status. However, household food insecurity had a negative correlation but did not significantly impact the nutritional status. Conclusion: Under-five malnutrition was prevalent in the study area and still a public health concern. Although the study did not find any significant association between household food wastage and food security towards the nutritional status of children, addressing the nutritional problem warranted an appropriate Public Health approach for the specific group, especially the modifiable risk factors such as birth weights, appetite, and attitude.